(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2011)
The Permian litho- and biostratigraphy of the Darin and Gachal sections of the southern part of the Kalmard block, Central Iran, are described. Like the Permian in the Halvan Mountain sections of the northern part of the block, the southern sections include four formations, namely the Chili, Chah-Kular, Hermez, and Rizi. The Chah-Kular Formation, which is first established in the present paper, corresponds to the Sartakht Formation of the northern sections. Its lowest beds contain plant fossils characteristic of the Lower Permian of Europe and partly, China. The Chili Formation includes fusulinids of the Kalaktashian assemblage, which has been dated as Sakmarian based on conodonts. Fusulinids in the Halvan Mt. section, which appear at the top of the formation, were previously found in conglomerate pebbles at the base of the overlying Sartakht Formation. As the beds with the Halvan Mt. fusulinid assemblage occur above beds with late Sakmarian conodonts, the assemblage may be of Artinskian age. However, that assemblage includes taxa usually not present either in the Artinskian fusulinid assemblage of the Urals or in the fusulinids of the Yakhtashian Stage that succeeds the Sakmarian in the Tethyan scale. A new fusulinid species (Nonpseudofusulina darinensis Leven, sp. nov.) and plants Annularia carinata Gutbier, Pecopteris monyi Zeiller P. cyathea (Schlotheim) Brongniart, Fascipteris cf. robusta (Kawasaki) Broutin, Discinites sp., Taeniopteris cf. crassicaulis Jongmans & Gothan are described. Palaeogeography of Central Iran region and adjacent areas is discussed.